Relationships Between WUT (Body Weight, Urine Color, and Thirst Level) Criteria and Urine Indices of Hydration Status. (July 2022) - Sekiguchi, Yasuki; Benjamin, Courteney L.; Butler, Cody R.; Morrissey, Margaret C.; Filep, Erica M.; Stearns, Rebecca L.; Lee, Elaine C.; Casa, Douglas J.
Background: A Venn diagram consisting of percentage body mass loss, urine color, and thirst perception (weight, urine, thirst [WUT]) has been suggested as a practical method to assess hydration status. However, no study to date has examined relationships between WUT and urine hydration indices. Thus, the purpose of this study was to investigate relationships between urine specific gravity, urine osmolality, and the WUT criteria. Hypothesis: Urine specific gravity and urine osmolality indicate hypohydration when the WUT criteria demonstrate hypohydration (≥2 markers). Study Design: Laboratory cohort study. Level of Evidence: Level 3. Methods: A total of 22 women (mean ± SD; age, 20 ± 1 years; mass, 65.4 ± 12.6 kg) and 21 men (age, 21 ± 1 years; body mass, 78.7 ± 14.6 kg) participated in this study. First morning body mass, urine color, urine specific gravity, urine osmolality, and thirst level were collected for 10 consecutive days in a free-living situation. Body mass loss >1%, urine color >5, and thirst level ≥5 were used as the dehydration thresholds. The number of markers that indicated dehydration levels were counted and categorized into either 3, 2, 1, or 0 WUT markers that indicated dehydration. One-way analysis of variance with Tukey pairwise comparisons was used to assess the differences in urine specific gravity and urine osmolality between the different number of WUT markers. Results: Urine specific gravity in 3 WUT markers (mean ± SD [effect size], 1.021 ± 0.007 [0.57]; P = 0.025) and 2 WUT markers (1.019 ± 0.010 [0.31]; P = 0.026) was significantly higher than 1 WUT marker (1.016 ± 0.009). Urine mosmolality in 2 WUT markers (705 ± 253 mOsmol [0.43]; P = 0.018) was significantly higher than 1 WUT (597 ± 253 mOsmol). Meeting at 3 WUT resulted in specificity of 0.956 and at 0 WUT resulted in sensitivity of 0.937 for urine osmolality>700mOsm. Conclusion: These results suggest that when 3 WUT markers are met, urine specific gravity and urine osmolality indicated hypohydration and 0 WUT represents a high likelihood of euhydration. 1 and 2 WUT values are indeterminate of hydration status. The WUT criterion is a useful tool to use in field settings to assess hydration status when first morning urine sample was used. Clinical Relevance: Athletes, coaches, sports scientists, and medical professionals can use WUT criteria to monitor dehydration with reduced cost and time.